Shabanovia, a new generic replacement name for Furia Egorova and Shabanov, 1987 (Trilobita) non Linnaeus, 1758 (Vermes) nec Cuvier, 1828 (Mammalia), preoccupied - Doweld, Alexander B. (Zootaxa, 2013)
The generic name Furia (F. submissa Egorova and Shabanov, 1987, by original designation) was proposed by Egorova and Shabanov (1987, p. 74) for a new trilobite genus from the middle Cambrian of Yakutia, Siberia. However, this name is already preoccupied by Furia Linnaeus (1758, p. 644). To resolve homonymy, in accordance with the International Code of Zoological Nomenclature, Shabanovia nom. nov. (type species Furia submissa Egorova and Shabanov, 1987) is here proposed as a replacement name for Furia Egorova and Shabanov non Linnaeus nec Cuvier to honor the name of Yury Yakovlevitch Shabanov, eminent Russian stratigrapher of Siberia.